2018
DOI: 10.1007/s11274-018-2477-9
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of aliphatic nitriles by the arylacetonitrilase from Pseudomonas fluorescens EBC191

Abstract: The conversion of aliphatic nitriles by the arylacetonitrilase from Pseudomonas fluorescens EBC191 (NitA) was analyzed. The nitrilase hydrolysed a wide range of aliphatic mono- and dinitriles and showed a preference for unsaturated aliphatic substrates containing 5-6 carbon atoms. In addition, increased reaction rates were also found for aliphatic nitriles carrying electron withdrawing substituents (e.g. chloro- or hydroxy-groups) close to the nitrile group. Aliphatic dinitriles were attacked only at one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…5). For example, we observed that Pseudomonas fluorescens NitA (Nit3 in our study) exhibited both arylacetonitrilase and aliphatic nitrilase activities, confirming previous reports 22 .…”
Section: Comparison Of Enzymatic Substrate Specificitysupporting
confidence: 92%
“…5). For example, we observed that Pseudomonas fluorescens NitA (Nit3 in our study) exhibited both arylacetonitrilase and aliphatic nitrilase activities, confirming previous reports 22 .…”
Section: Comparison Of Enzymatic Substrate Specificitysupporting
confidence: 92%
“…The reaction of HCN was terminated by adding 1.0 mL of methanol and centrifugation. The activities for β-CA were calculated from the production of ammonia, which was determined spectrophotometrically [11,49]. The activities for HCN were determined from the production of formamide, which was determined spectrophotometrically [50] and by HPLC (see below).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial NLases were usually classified into a number of substrate-specificity subtypes, i.e., aromatic NLases, aliphatic NLases, arylacetoNLases, bromoxynil-specific NLases, CynHs and CynDs [7]. However, a recent study suggested that aliphatic NLases may not actually exist, since the activities for aliphatic nitriles are present in other NLase types such as arylacetoNLases [11]. The plant NLases could be classified into two main subtypes, namely NIT1 through NIT3 with broad substrate specificities on the one hand [12] and NIT4 with a strict specificity for β-cyanoalanine (β-CA) on the other [13].…”
Section: Introductionmentioning
confidence: 99%
“…The ''bienzymatic catalysts'' described in the present manuscript in combination with the previously constructed recombinant strains which simultaneously express the (S)-specific oxynitrilase from cassava together with the nitrilase(variants) allow the facile synthesis of a wide range of chiral hydroxycarboxylic acids and amides from simple precursors. This can be deduced from the ''proof of principle'' experiments described in this and previous publications for the ''bienzymatic catalysts'' and the substrate ranges of the used nitrilase and oxynitrilases which demonstrated for all three enzymes (the oxynitrilases from cassava and Arabidoposis thaliana and the nitrilase from P. fluorescens EBC 191) rather broad substrate specifities (Andexer et al 2007;Baum et al 2012;Brunner et al 2018;Bühler et al 2003;Kiziak et al 2005, Sosedov et al 2009.…”
Section: Discussionmentioning
confidence: 72%